Implementasi Sister City Kota Semarang Dengan Kota Fuzhou - Reyva Fernanda Priskilla; Susiatiningsih Hermini; Alfian Muhammad Faizal (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
ABSTRACTIn Indonesia, the Sister City concept began to be known as the circulation of the Ministry of Home Affairs Circular No. 193/1652/PUOD on April 26, 1993 concerning Procedures for Formation of Cities and Inter -Provincial Cooperation (Sister Province). The concept of sister city in Indonesia has been established by several regions with the equality of technology, education, culture and history with other regions abroad. In this study there is the purpose of this study to explore the implementation of Sister City Semarang City with Fuzhou City.In this study there are benefits that can be a reference for other regional governments, the private sector, the community and other researchers in establishing cooperative relations with abroad. To answer the problems and research objectives is carried out using the concept of paradlomation and sister city with interview methods and data reviews. The object in this study was the Semarang City Government. Paradiplomation in the Sister City sister of Semarang City with Fuzhou City can be seen from the implementation and benefits in the fields of economics, education, and the fields of culture and tourism. So that the existence of activities that produce results show that the paradlomacy can run with good cooperation between local governments.For example, Indonesia has continuously been praised as a successful post-authoritarian country transitioning to democracy. However, seeing the numerous human rights violations in the past decade alone, especially towards alternative political, religious, and sexual identities, the success of democracy in Indonesia has been put under the spotlight. It raises the question of the development of democracy and the use of democracy in Indonesia in practicing and upholding principles of social equality for all. In this article, I wish to provide an overview of majoritarian democracy, a form of democracy that is understood and practiced in Indonesia. A form of democracy that, rather than upholding values that safeguards individual rights and diversity, may undermine religious and cultural diversity, enforcing a homogenized national culture and values, which in return may engender human rights violations in the name of national security that it in itself is defined by the majority..Keywords: Paradiplomacy, Sister City, Semarang City, Fuzhou City